Stepwise Assembly of an Electroactive Framework from a Co6S8 Superatomic Metalloligand and Cuprous Iodide Building Units. Issue 55 (1st September 2020) - Freeman, Matthew B.; Edokobi, Ozioma D.; Gillen, Jonathan H.; Kocherga, Margaret; Dipple, Kathleen M.; Jones, Daniel S.; Paley, Daniel W.; Wang, Le; Bejger, Christopher M.
Abstract: Invited for the cover of this issue is Christopher Bejger and co‐workers at UNC Charlotte, Columbia University, and Donghua University. The image depicts a pair of star clusters in the constellation Perseus as the structure of two metal clusters in the reported framework. Read the full text of the article at 10.1002/chem.20201215 . Abstract : " We found that we can prepare atomically precise coordination polymers containing two different metal‐cluster units. The way in which this material was synthesized is also noteworthy. Most heterobimetallic frameworks are made via one‐pot protocols. Our team used a stepwise approach with a discrete Co6 S8 "superatom" building block serving as the monomer ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 12523 ff. (DOI: 10.1002/chem.202001215 ).